Improving Signatures by Locality Exploitation for Transactional Memory - Quislant-del-Barrio, Ricardo; Gutiérrez-Carrasco, Eladio Damián; Plata-González, Óscar Guillermo; López-Zapata, Emilio (IEEE, 2009)
Writing multithreaded programs is a fairly complex task that poses a major obstacle to exploit multicore processors. Transactional Memory (TM) emerges as an alternative to the conventional multithreaded programming to ease the writing of concurrent programs. Hardware Transactional Memory (HTM) implements most of the required mechanisms of TM at the core level, e.g. conflict detection. Signatures are designed to support the detection of conflicts amongst concurrent transactions, and are usually implemented as per-thread Bloom filters in HTM. Basically, signatures use fixed hardware to summarize an unbounded amount of read and write memory addresses at the cost of false conflicts (detection of non-existing conflicts). In this paper, a novel signature design that exploit locality is proposed to reduce the number of false conflicts. We show how that reduction translates into a performance improvement in the execution of concurrent transactions. Our signatures are based on address mappings of the hash functions that reduce the number of bits inserted in the filter for those addresses nearby located. This is specially favorable for large transactions, that usually exhibit some amount of spatial locality. Furthermore, the implementation do not require extra hardware. Our proposal was experimentally evaluated using the Wisconsin GEMS simulator and all codes from the STAMP benchmark suite. Results show a significant performance improvement in many cases, specially for those codes with long-running, large-data transactions.
Keywords: Ordenadores - Memorias; Hardware transactional memory; Signatures; Bloom filters; H3 hashing; Memory locality